Discussing Pax Germanica : the rise and limits of German hegemony in European integration - Comte, Emmanuel, 1960-; Guirao, Fernando, 1962- (London ; New York, NY : Routledge, Taylor & Francis Group, 2025)
"Discussing Pax Germanica: The Rise and Limits of German Hegemony in European Integration examines and reconsiders Germany's paramount role in shaping European integration from the aftermath of World War II to the present. Targeting a diverse audience of both scholars and non-specialists, this book is particularly relevant for those interested in European politics, German history, and international relations"--
The European Union of the German nation / Emmanuel Comte and Brendan Simms -- The Habsburg peace and its lessons for today's Europe / Caroline de Gruyter -- Economics and power in German national identity / Harold James -- The sources and effects of German hegemony on European integration / Emmanuel Comte -- Germany and France -- The elusiveness of a joint hegemony / Wolf Lepenies -- How Helmut Schmidt and Helmut Kohl made Europe / Kristina Spohr -- Testimony : German pre-eminence in Europe / Herman Van Rompuy -- Spectres of German dominance : anxieties aroused and averted since 1950 / Charles S. Maier -- Solving the German question through European integration / Wilfried Loth -- European integration history revisited around German leadership in the European Monetary System / Fernando Guirao -- The failure of German hegemony in European energy policy / Stephen Gross -- German hegemony in the European Union? Evaluating the 'crisis years' from 2010 / Simon Bulmer and William Paterson -- Hegemony and Germany : an odd couple / Joachim Schild.
Keywords: Germany -- Foreign relations -- 1945-; Germany -- Foreign relations -- European Union countries; European Union countries -- Foreign relations -- Germany; Germany -- Politics and government -- 1945-1990.; Germany -- Politics and government -- 1990-; Germany -- Politics and government -- 20th century; Germany -- Economic conditions -- 20th century; HISTORY / Europe / Germany; HISTORY / Europe / Eastern; HISTORY / Europe / Russia & the Former Soviet Union